Plasma carotenoids, vitamin C, retinol and tocopherols levels and pancreatic cancer risk within the European Prospective Investigation into Cancer and Nutrition: A nested case–control study. Issue 6 (17th September 2014) - Jeurnink, Suzanne M.; Ros, Martine M.; Leenders, Max; van Duijnhoven, Franzel J.B.; Siersema, Peter D.; Jansen, Eugene H.J.M.; van Gils, Carla H.; Bakker, Marije F.; Overvad, Kim; Roswall, Nina; Tjønneland, Anne; Boutron‐Ruault, Marie‐Christine; et al.
<x xml:space="preserve">Abstract</x> Evidence of a protective effect of several antioxidants and other nutrients on pancreatic cancer risk is inconsistent. The aim of this study was to investigate the association for prediagnostic plasma levels of carotenoids, vitamin C, retinol and tocopherols with risk of pancreatic cancer in a case–control study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC). 446 incident exocrine pancreatic cancer cases were matched to 446 controls by age at blood collection, study center, sex, date and time of blood collection, fasting status and hormone use. Plasma carotenoids (α‐ and β‐carotene, lycopene, β‐cryptoxanthin, canthaxanthin, zeaxanthin and lutein), α‐ and γ‐tocopherol and retinol were measured by reverse phase high‐performance liquid chromatography and plasma vitamin C by a colorimetric assay. Incidence rate ratios (IRRs) with 95% confidence intervals (95%CIs) for pancreatic cancer risk were estimated using a conditional logistic regression analysis, adjusted for smoking status, smoking duration and intensity, waist circumference, cotinine levels and diabetes status. Inverse associations with pancreatic cancer risk were found for plasma β‐carotene (IRR highest vs. lowest quartile 0.52, 95%CI 0.31–0.88, p for trend = 0.02), zeaxanthin (IRR highest vs. lowest quartile 0.53, 95%CI 0.30–0.94, p for trend = 0.06) and α‐tocopherol (IRR highest vs. lowest quartile 0.62, 95%CI 0.39–0.99, p for trend = 0.08. For α‐ and β‐carotene, lutein, sum of carotenoids and γ‐tocopherol, heterogeneity between geographical regions was observed. In conclusion, our results show that higher plasma concentrations of β‐carotene, zeaxanthin and α‐tocopherol may be inversely associated with risk of pancreatic cancer, but further studies are warranted.